Obstructive jaundice due to the lower bile duct lesions: biliary drainage and predictive factors of postoperative complications - CHIJIIWA, Kazuo; YOSHIDA, Junichi; SHIMURA, Hideo; KINUKAWA, Naoko; SATO, Hiroshi; YAMAGUCHI, Koji; TANAKA, Masao (Tando, 1996)
We studied the effect of biliary decompression and operative risk in patients with obstructive jaundice. Subjects were a consecutive series of patients (n=42) in the past 10 years excluding those with calculi. Bile was drained by means of percutaneous transhepatic, endoscopic, or cholecystostomy method. We statistically analyzed predictive factors of postoperative complications such that developed in nine (21%) of our patients. Comparing factors before and after biliary drainage, the levels of total bilirubin, transaminases, alkaline phosphatase, lactic dehydrogenase, and rglutamic transpeptidase were significantly decreased. A multivariate analysis revealed that predrainage platelet count and post-drainage platelet count and creatinine level correlated positively with postoperative complications. Little was described in the literature on the platelet count as a poor risk factor. In conclusion, icteric patients having an increased number of platelet or renal dysfunction would dictate less invasive procedures or close postoperative management.